Proposing waqf percentage model (WPM) in the context of higher education - Allah Pitchay, Anwar; Abd Jalil, Mohamad Isa; Soekarno, Megawati; Mohd Thas Thaker, Mohamed Asmy (UMS Press, 2020)
One of the critical hurdles for universities in the next decade will be financial sustainability. Only those institutions that have stable economic structures and steady income flows will be able to accomplish their numerous undertakings and counter any current and upcoming challenges. This article is proposing the model of cash Waqf by income percentage within the higher education context. The proposed model was shown to an expert to develop a greater understanding of the Waqf Percentage Model (WPM) as well as appraise its applicability, suitability and prospects in the market. The discoveries from the interviews have supported the appropriateness of the Waqf Percentage Model in providing significant financial amenities. Consequently, the model is thought to be extremely beneficial in providing financial amenities by providing a substitute for conventional monetary establishments. The government should consider it carefully as this model could help them to reduce expenses on Waqf development. Finally, the Waqf Percentage Model can also be adopted by the Waqf institutions of other Muslim countries.